External Effects of 'Daddy Months': How Fathers' Parental Leave Changes Social Norms - Katharina Wrohlich; Ulrike Unterhofer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We analyze whether the introduction of the fathers' quota in parental leave in 2007 has changed the gender roles attitudes in the grandparents' generation. Exploting the quasi-experimental setting of the reform, we find a positive effect of the fathers' quota on attitudes towards gender equality. The results suggest that such programs not only induce direct behavioral responses by the target group but also have indirect effects on other groups through social interaction.
Keywords: 330